THE EFFECT OF TOURIST PARENTS’ COGNITIVE AND AFFECTIVE TRUST IN KIDS CLUB EMPLOYEES ON CUSTOMER SATISFACTION AND INTENTION TO RECOMMEND - Çağıl Hale Özel (PEOPLE: International Journal of Social Sciences, 2025)
This project is about the trust relationship between parents traveling within the scope of family tourism and employees working in kids clubs of hotels. As it is known, tourists traveling within the scope of family tourism leave their children in kids clubs located in child-friendly hotels for both fun and learning during their stay. For this reason, issues such as the sufficient number of personnel employed in kids clubs, their job qualifications and the ability of these personnel to communicate effectively with children are gaining importance. One of the most important characteristics that the personnel working in kids clubs should have is reliability. Among the previous studies in the literature, no research examining the trust relationship between kids club employees and tourists (parents) has been found. Based on this determination, the trust that tourist parents have in kids club personnel is examined in the context of Interpersonal Relationship Theory in this study. In addition, the effect of cognitive and affective trust in kids club employees on customer satisfaction and intention to recommend is investigated in the study. The aim of the study is to determine the effect of cognitive and affective trust that parents have in employees working in kids clubs of hotels on customer satisfaction and intention to recommend. In this way, it will be possible to determine the level of cognitive and affective trust in kids club employees and whether this trust affects customer satisfaction and intention to recommend through the eyes of parents. In order to achieve this aim, parents who have received service from kids clubs during their hotel stays in Turkey in the last five years will be contacted by face to face and/or online questionnaires and data will be collected from them. The data will be tested using a quantitative research design and appropriate analyses, and the hypotheses created will be tested. The findings reached in the study will be presented to the attention of practitioners in order to improve the service provided by employees in kids clubs and will contribute to businesses in terms of making a difference with the services of kids clubs. The most important contribution of the study to the field is to identify the points where kids club employees of hotels fall short in providing services and to develop in-service trainings in this direction, and to create awareness in a broader context for the determination of guiding principles including parameters such as “accommodation, food and beverage, health and safety-employees” for child-friendly hotels in Turkey.